Choosing the Appropriate Assistive Device: A Card-Sorting Activity - Maria van Zuilen; Osvaldo Rodriguez; Miguel Paniagua; Michael Mintzer (Association of American Medical Colleges, 2008)
Abstract Introduction This resource is a 30-40 minute instructional activity designed for small groups of six to eight medical trainees to apply basic information learned about assistive devices. Although this session is intended for learners who have received some preliminary instruction on assistive devices, it can be modified readily to be the primary instructional modality for learners who have had little previous exposure. Methods This interactive teaching activity uses a card-sorting format in which participants are given a set of cards, each containing a different patient scenario, and are asked to match each card with one of seven assistive devices displayed on a table. Once the matches are complete, participants discuss the rationale for their matches and, with input from the group members, make needed changes. The facilitator encourages further group discussion to clarify any misconceptions or mismatches. Key points about the use of assistive devices and common mistakes in their use are reinforced. Results One-hundred and sixty-six second-year medical students participated in this small-group activity in the spring of 2007 and completed a postsession evaluation form. They rated the session very positively. Participation in the session helped students prepare for an end-of-year online competency assessment in which they were asked to match assistive devices to patient conditions, a skill they practiced in this session. Discussion We have conducted this session with second-year medical students. At the time of the session, one of our fourth-year students rotating through the nursing home had a background in physical therapy. He volunteered to facilitate some of the sessions and he received very positive feedback from the students. We have found that with a detailed facilitator's guide, advanced medical students and members from other disciplines can successfully conduct this and some of our other teaching sessions. It is helpful if facilitators have a background in working with older adults, as this allows them to draw on their own experience during the group discussions.